Design of a sensorized guiding catheter for in situ laser fenestration of endovascular stent. Issue 1 (1st January 2017) - Piazza, Roberta; Condino, Sara; Alberti, Aldo; Berchiolli, Raffaella Nice; Coppi, Gioachino; Gesi, Marco; Ferrari, Vincenzo; Ferrari, Mauro
Abstract: Purpose: The in situ fenestration of a standard endograft is currently limited by difficulties in targeting the fenestration site under fluoroscopic control and by the lack of a safe method to perforate the graft. Evidence in the literature suggests the use of a 3 D electromagnetic navigator to accurately guide the endovascular instruments to the target and a laser to selectively perforate the graft. The aim of this work is to provide design guidelines to develop a sensorized catheter to guide the laser tool to the fenestration site and conduct preliminary testing of the feasibility of the proposed solution. Matherials and methods: Different catheter designs were delineated starting from engineering considerations, then prototypes were preliminarily tested to collect surgeon opinions and to steer the design process toward the preferred solution reported by the user. Finally, mechanical simulations were performed with CathCAD, a design software system for the development of composite tubing for endovascular catheters. Results: Based on surgeon feedback, a 9-French steerable catheter with a stabilization system was designed. CathCAD simulations allowed us to define the construction parameters (e.g., materials and geometric constrains) for the fabrication of composite tubes with mechanical properties (flexural, axial, and torsional rigidities) compatible with target values in the literature for guiding catheters. Conclusion: The presented results preliminarily demonstrate the clinical reasonability and feasibility of the designed tool in terms of mechanical properties. Further mechanical tests and extensive in vitro clinical trials are required prior to animal testing.